2022
DOI: 10.1002/adom.202201572
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerized Triphenylamine Network Films for High‐Performance Transparent to Black Electrochromism and Capacitance

Abstract: can only be called black ECMs. Therefore, in addition to the general electrochromic performance parameters such as contrast ratio, response time, and cyclic stability, for transparent to black ECMs, the satisfactory bleached state is as important as the good black colored state.Conjugated triphenylamine (TPA)based polymers are a kind of potential transparent to black ECMs. [5] TPA cation has strong absorption range of 500-720 nm; [6] N,N,N′,N′-Tetraphenylbenzidine (TPB) is a common bridged structure of polytr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…30,35 However, polymeric or hybrid electrochromic systems have seemed to deliver better energy storage properties. 36–43 In this direction, our research group is currently focusing on developing EC hybrid materials to improve energy storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,35 However, polymeric or hybrid electrochromic systems have seemed to deliver better energy storage properties. 36–43 In this direction, our research group is currently focusing on developing EC hybrid materials to improve energy storage.…”
Section: Resultsmentioning
confidence: 99%
“…However, not much research has been reported on organic small molecules as multifunctional EC systems with energy storage ability to compare our 30,35 However, polymeric or hybrid electrochromic systems have seemed to deliver better energy storage properties. [36][37][38][39][40][41][42][43] In this direction, our research group is currently focusing on developing EC hybrid materials to improve energy storage.…”
Section: Energy Storage Studiesmentioning
confidence: 99%
“…Based on the references, the first sharp peak drop from the discharge profile is mainly attributed to the material's double-layer capacitive discharge, followed by the phase transformation plateau with an extended discharge time for reactant diffusion into the inner pores for the battery-type reaction, and the final drop can be attributed to the concentration polarization of the material. 54–56…”
Section: Resultsmentioning
confidence: 99%
“…Based on the references, the rst sharp peak drop from the discharge prole is mainly attributed to the material's double-layer capacitive discharge, followed by the phase transformation plateau with an extended discharge time for reactant diffusion into the inner pores for the battery-type reaction, and the nal drop can be attributed to the concentration polarization of the material. [54][55][56] In Fig. S33a, † TPPA-Ether exhibited a symmetric chargedischarge characteristic pattern with a specic capacitance (C sp ) of 111.8 F g −1 at 1.0 A g −1 and a coulombic efficiency of 93.5% and could remain high C sp of 97.5 F g −1 even in the case of high current density (10 A g −1 ).…”
Section: Capacitive Properties Of Polyamide Lmsmentioning
confidence: 99%
“…Organic materials such as conducting polymers and viologens have recently become an intensive research topic. The conducting polymers have several advantages over inorganic compounds as EC materials, including good electrochemical stability, fast switching speed, high coloring efficiency (CE), easy large-area processing, and color tuning through chemical modification. Also, triphenylamine (TPA)-containing polymers have been developed as an attractive family of EC materials because of their colorless neutral state and intriguing EC behaviors. In recent years, redox-active materials with optical absorption change in the near IR (NIR) region have drawn significant attention due to their potential applications in optical communication, data storage, and thermal control in buildings and spacecraft. , For example, Wan et al reported that the quinone-containing EC materials revealed high absorption in NIR upon electrochemical reduction . Reynolds and Beaujuge reported that the conjugated polymers could exhibit multicolor in the neutral state and transmission in the oxidized state. , Liou and Lin also noted that the TPA-based polymers demonstrated an attractive anodic EC system for NIR applications due to their particular intramolecular electron transfer in the oxidized forms …”
Section: Introductionmentioning
confidence: 99%